The CPWF Working Paper series: Proposed new directions and notes for Contributors - Victor, Michael; Brakel, Martin L. van (CGIAR Challenge Program on Water and Food, 2011)
These guidelines provide researchers with an overview of the CPWF working papers series and how to submit potential papers for the series.